2018
DOI: 10.2147/amep.s173470
|View full text |Cite
|
Sign up to set email alerts
|

Pre-matriculation clinical experience positively correlates with Step 1 and Step 2 scores

Abstract: BackgroundThis study investigates whether students with pre-matriculation, formalized, clinical experience performed better in Step 1 and Step 2 of the United States Medical Licensing Exams (USMLE) compared to students without formal pre-matriculation clinical experience.MethodsThis research investigation was a retrospective cohort study conducted at the University of Arizona College of Medicine in Tucson, Arizona, USA, and analyzed students in the Class of 2017 and Class of 2018. Formal clinical experience wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
11
1
Order By: Relevance
“…While the majority of them noted that their scribe experience helped them "somewhat" or "a lot" with their pre-clerkship work, an analysis of covariance (ANCOVA) found no statistically significant difference in outcome metrics such as USMLE (United States Medical Licensing Examination) Step 1 scores, class rank, assessment of note writing ability, or self-reported wellbeing. This finding contrasts with that of Shah et al [18] who found a statistically significant improvement in both Step 1 and Step 2 USMLE scores for those with "pre-matriculation clinical experience" among a single class of medical students at one school. It must be noted however that Shah did not assess the impact of having been a scribe separately from the other forms of "pre-matriculation experience" (e.g., having been an RN/LPN/NP, PA, or EMT/paramedic) and it is not possible to conclude from this that scribing itself is linked with subsequent improved exam performance.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…While the majority of them noted that their scribe experience helped them "somewhat" or "a lot" with their pre-clerkship work, an analysis of covariance (ANCOVA) found no statistically significant difference in outcome metrics such as USMLE (United States Medical Licensing Examination) Step 1 scores, class rank, assessment of note writing ability, or self-reported wellbeing. This finding contrasts with that of Shah et al [18] who found a statistically significant improvement in both Step 1 and Step 2 USMLE scores for those with "pre-matriculation clinical experience" among a single class of medical students at one school. It must be noted however that Shah did not assess the impact of having been a scribe separately from the other forms of "pre-matriculation experience" (e.g., having been an RN/LPN/NP, PA, or EMT/paramedic) and it is not possible to conclude from this that scribing itself is linked with subsequent improved exam performance.…”
Section: Discussioncontrasting
confidence: 99%
“…The belief that having been a scribe improves a student's ability to succeed in medical school has little scientific foundation in the literature beyond some reports on performance on standardized exams and clerkship grades [17][18][19][20][21][22]. We are particularly interested in the perceptions of students who have been scribes.…”
Section: Introductionmentioning
confidence: 99%
“…Medical College Admission Test (MCAT): Many studies have shown that the MCAT score was a strong predictor for Step 2 CK score [ 36 , 41 ]. Two studies (p = 0.04 and p < 0.001) showed that a positive relationship exists when using the older style of MCAT scoring in regard to Step 2 CK performance [ 42 ].…”
Section: Reviewmentioning
confidence: 99%
“…Pre-matriculation programs have been implemented in the past in order to benefit students of lower socioeconomic status in terms of transitioning and succeeding in medical school (Shah et al, 2018). These past programs have proven to be highly successful in that participants within these programs reportedly felt that it eased the transition to medical school, increased levels of confidence, and provided opportunities to socially interact with peers and mentors (Kornitzer, Ronan and Rifkin, 2005).…”
Section: Discussionmentioning
confidence: 99%